2020
DOI: 10.1089/cbr.2019.3259
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MIAT Regulates Cell Growth, Migration, and Invasion Through Sponging miR-150-5p in Ovarian Cancer

Abstract: Background: MIAT (myocardial infarction-associated transcript) regulates cell proliferation, apoptosis, and metastasis in several cancers. In this study, the authors aimed to explore the role of MIAT in ovarian cancer. Materials and Methods: The expression of MIAT in ovarian cancer subtypes, normal human ovarian surface epithelial and ovarian cancer cell lines was measured by qualitative real-time polymerase chain reaction (qRT-PCR). OVCAR3 and SKOV3 cells were transfected with MIAT overexpression plasmid or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In colorectal cancer (CRC), LINC00460 was shown to serve as an oncogene of CRC that got involved in carcinogenesis by heightening the stabilization of HMGB1 at mRNA level [ 22 ]. As suggested by Zhou et al, MIAT could exert oncogenic role in regulation of cell growth and EMT through binding with miR-150-5p, providing a novel insight for the management of ovarian cancer [ 23 ]. Yao et al demonstrated that high expression MSC-AS1 could facilitate the malignant behavior of nasopharyngeal cancer via miR-524-5p/NR4A2 axis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), LINC00460 was shown to serve as an oncogene of CRC that got involved in carcinogenesis by heightening the stabilization of HMGB1 at mRNA level [ 22 ]. As suggested by Zhou et al, MIAT could exert oncogenic role in regulation of cell growth and EMT through binding with miR-150-5p, providing a novel insight for the management of ovarian cancer [ 23 ]. Yao et al demonstrated that high expression MSC-AS1 could facilitate the malignant behavior of nasopharyngeal cancer via miR-524-5p/NR4A2 axis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years multiple studies have emphasized the biological role of hsa-miR-150-5p in carcinogenesis [ 30–32 ]. Zhou et al reported that hsa-miR-150-5p was repressed by long non-coding RNA Myocardial Infarction Associated Transcript (lncRNA MIAT), and cell growth was increased by hsa-miR-150-5p mimics, and reversed by the overexpression of MIAT levels [ 30 ]. Tian et al suggested that hsa-miR-150-5p significantly repressed the Wnt/β-catenin signaling pathway to hamper the stem cell-like characteristics of glioma cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-150-5p has been validated to play important roles in the progression of different types of cancers by regulating lncRNAs. miR-150-5p has been detected to regulate ovarian cancer progression via the lncRNA MIAT ( Zhou et al, 2020 ). miR-150-5p has also been found to contribute to cell proliferation and migration of colorectal cancer with lncRNA PART1 ( Lou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%